Seasonal Distribution of Births in Anatolian Buffaloes and Effects of the Season on Some Milk and Reproductive Traits of Cows and Growth Traits of Calves - Hüseyin Erdem; İbrahim Cihangir Okuyucu; Savaş Atasever (Turkish Journal of Agriculture: Food Science and Technology)
The aims of this study were i) to evaluate the seasonal changes in births of Anatolian buffaloes, ii) to examine the changes of some milk [lactation milk yield (LMY) and lactation length (LL)] and fertility [first calving age (FCA) and calving interval (CI)] according to seasons and iii) to investigate the effects of seasons on the growth traits of calves [birth weight (BW0), live weight at 6 mo (LW6) and live weight at 12 mo (LW12)]. A total of 8614 to 15605 yield records were evaluated including milk yield and fertility traits of buffalo cows and growth traits of calves between 2012 and 2023. The mean temperature, relative humidity, the duration of sunshine, and temperature humidity index (THI) values were calculated for these years. While the highest birth rate was observed in the summer season (34.27%), the lowest birth rate was determined in the winter season (11.99%). The BW0, LW6 and LW12, LMY, LL, FCA, and CI values of the calves were determined as 30.8±0.04 kg, 107.6±0.23 kg, 172.6±0.27 kg, 994.7±2.05 kg, 262.6±0.22 d 1175.5±3.46 d and 561.7±1.84 d, respectively. Except for CI, all characteristics were significantly affected by seasonal changes (P<0.001). The growth traits of the calves born in autumn were higher than the other seasons. The LMY values in spring and winter were higher than those determined in the different seasons. Also, the highest FCA was obtained in heifers born in the winter. It was concluded that the season could affect both some fertility and milk yield characteristics of buffalo cows and the growth performance of calves.